Oxidation of 2-propanol and cyclohexane by the reagent "Hydrogen peroxide - Vanadate anion - Pyrazine-2-carboxylic acid": Kinetics and Mechanism - Kozlov, Yuriy N; Romakh, Vladimir B; Kitaygorodskiy, Alex; Buglyo, Peter; Süss-Fink, Georg; Shul'pin, Georgiy B (My University, 2007)
The vanadate anion in the presence of pyrazine-2-carboxylic acid (PCA equivalent to pcaH) efficiently catalyzes the oxidation of 2-propanol by hydrogen peroxide to give acetone. UV-vis spectroscopic monitoring of the reaction as well as the kinetics lead to the conclusion that the crucial step of the process is the monomolecular decomposition of a diperoxovanadium(V) complex containing the pca ligand to afford the peroxyl radical, HOO center dot and a V(IV) derivative. The rate-limiting step in the overall process may not be this (rapid) decomposition itself but (prior to this step) the slow hydrogen transfer from a coordinated H2O2 molecule to the oxygen atom of a pca ligand at the vanadium center: "(pca)(O)V center dot center dot center dot O2H2" -> "(pca)(HO-)V-OOH". The V(IV) derivative reacts with a new hydrogen peroxide molecule to generate the hydroxyl radical ("V-IV" + H2O2 -> "V-V" + HO- + HO center dot), active in the activation of isopropanol: HO center dot + Me2CH(OH) -> H2O + Me2C center dot(OH). The reaction with an alkane, RH, in acetonitrile proceeds analogously, and in this case the hydroxyl radical abstracts a hydrogen atom from the alkane: HO center dot + RH -> H2O + R-center dot. These conclusions are in a good agreement with the results obtained by Bell and co-workers (Khaliullin, R. Z.; Bell, A. T.; Head-Gordon, M. J. Phys. Chem. B 2005, 109, 17984-17992) who recently carried out a density functional theory study of the mechanism of radical generation in the reagent under discussion in acetonitrile.
Keywords: O-2-H2O2-VANADIUM DERIVATIVE-PYRAZINE-2-CARBOXYLIC ACID; LIQUID-PHASE; OXIDATION; H2O2-VANADIUM COMPLEX-PYRAZINE-2-CARBOXYLIC ACID; HYDROXYL; RADICAL FORMATION; MODIFIED SILICA-GEL; V-51 NMR; AQUEOUS-SOLUTION; VANADIUM CATALYSTS; AEROBIC OXIDATION; HYDROCARBON OXIDATIONS